Pengaruh Olahraga Teratur Terhadap Kesehatan Mental Remaja - Nimrot Manalu; Samuel Tampubolon; Orlando Pangihutan; Anugrah Rizky; Syuhada Muslim; Teguh Ilham; Gerhard Yosafat; Maykel Octaloren; Miftahul Ihsan; Andes Martua (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of regular exercise on adolescent mental health. The study was conducted using a quantitative method using a quasi-experimental approach. A total of 10 adolescents aged 15–18 years were divided into two groups: an experimental group that did regular exercise for 1 week and a control group that was not given special treatment. The results showed that there were significant differences in stress, anxiety, and mood levels between the two groups. Regular exercise has been shown to significantly improve adolescent mental health. This study aims to determine the effect of regular exercise on adolescent mental health. The study was conducted using a quantitative method using a quasi-experimental approach. A total of 10 adolescents aged 15–18 years were divided into two groups: an experimental group that did regular exercise for 1 week and a control group that was not given special treatment. The results showed that there were significant differences in stress, anxiety, and mood levels between the two groups. Regular exercise has been shown to significantly improve adolescent mental health.